ANALISIS SEMIOTIKA DALAM KESENIAN KUDA LUMPING BIMA SAKTI - Reni Juliani; Rahma Hidayati; Winda Trisniawati (SOURCE : Jurnal Ilmu Komunikasi, 2019)
This research aims to determine the meaning of Kuda Lumping Bima Sakti Art performance. The research method used is descriptive qualitative. The main research informant was Jono Suwito as an elder and handler in Kuda Lumping Bima Sakti Art. Research data was collected by conducting direct observation, interviews and documentation. The results of this research indicated that the meaning of denotation of Kuda Lumping Bima Sakti Art as a whole is a show that in every movement there is a bond of dance in culture. There are also meanings of a community life and a religious belief. The connotation meaning of Kuda Lumping Bima Sakti Art is how to respond and believe that every culture has its own beliefs and from this connotation meaning, human must believe that God and supernatural exist. And the meaning of myth of Kuda Lumping Bima Sakti Art is that in daily life humans cannot be seperated from supernatural matters. Then the key to all of Kuda Lumping Bima Sakti Art rituals is that all movements have meaning from where the dance originated. The main key is to remind humans of God or return to their origin, namely the Creator.Keywords: Semiotics, Kuda Lumping, and Bima Sakti